Characterization of a highly conserved MUC5B-degrading protease, MdpL, from Limosilactobacillus fermentum - Leo, Fredrik; Svensäter, Gunnel; Lood, Rolf; Wickström, Claes (Frontiers in Microbiology, 2023)
MUC5B is the predominant glycoprotein in saliva and is instrumental in the establishment and maintenance of multi-species eubiotic biofilms in the oral cavity. Investigations of the aciduric Lactobacillaceae family, and its role in biofilms emphasizes the diversity across different genera of the proteolytic systems involved in the nutritional utilization of mucins. We have characterized a protease from Limosilactobacillus fermentum, MdpL (Mucin degrading protease from Limosilactobacillus) with a high protein backbone similarity with commensals that exploit mucins for attachment and nutrition. MdpL was shown to be associated with the bacterial cell surface, in close proximity to MUC5B, which was sequentially degraded into low molecular weight fragments. Mapping the substrate preference revealed multiple hydrolytic sites of proteins with a high O-glycan occurrence, although hydrolysis was not dependent on the presence of O-glycans. However, since proteolysis of immunoglobulins was absent, and general protease activity was low, a preference for glycoproteins similar to MUC5B in terms of glycosylation and structure is suggested. MdpL preferentially hydrolyzed C-terminally located hydrophobic residues in peptides larger than 20 amino acids, which hinted at a limited sequence preference. To secure proper enzyme folding and optimal conditions for activity, L. fermentum incorporates a complex system that establishes a reducing environment. The importance of overall reducing conditions was confirmed by the activity boosting effect of the added reducing agents L-cysteine and DTT. High activity was retained in low to neutral pH 5.5-7.0, but the enzyme was completely inhibited in the presence of Zn2+. Here we have characterized a highly conserved mucin degrading protease from L. fermentum. MdpL, that together with the recently discovered O-glycanase and O-glycoprotease enzyme groups, increases our understanding of mucin degradation and complex biofilm dynamics.